Ekonomi Syariah Sebagai Fondasi Ekonomi Kerakyatan Untuk Mencapai Indonesia Yang Sejahtera - Zakaria Batubara (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2012)
The article below tries to subscribe the potential of Islamic sharia economics to solve Indonesian cases in economic aspect. One of its cases was the poorness of people in Indonesia more than half of its population, then in this article tries to find system of economic in Indonesian country first, so describes the value of Islamic sharia economics and internalized it in Indonesia system of economic. Islam as the last religion revealed by Allah SWT has many tools to anticipate and solve contemporary problems occurring in the global era. Al-Quran and al-Sunnah as the main sources of Islamic law provide tools to make Islamic teachings always suitable for all time, namely by Islamic sharia economic can solve any economic problem in Indonesia, as As-Shidiqy said, that “Islamic economic is the muslim thinkers response to the economic challenges of their time. In this endeavourers they were aided by the Quran and the Sunnah as well as by reason and experience”.